ANALYSIS AND PREDICTION OF OVERPRESSURE CHARACTERISTIC IN SOUTH SESULU FIELD, KUTAI BASIN, EAST KALIMANTAN - Luther M, Yosia
This study area is located at South Sesulu Field in the Kutai Basin. The stratigraphy of the study area consists of Bebulu Group, Balikpapan Group, Kampung Baru Group, dan Mahakam Group which are Early Miocene to Quarternary in age. The purposes of this study are to estimate pore pressure magnitude, determine the distribution of top of overpressure, analyse overpressure generating mechanism, and analyse the relationship between overpressure occurrence and geological condition in the study area. The analysis was performed in five offshore wells in South Sesulu Field, by using wireline log (gamma ray, density, sonic, and resistivity log), pressure data, vitrinite reflectance data, and well report. Based on data processing and analysis, it is known that there are three wells penetrating overpressure zone, i.e KMN-17, HNT-3, and GAP-5. The top of overpressure in KMN-17, HNT-3, and GAP-5 is located at the depth of 7949 feet with the magnitude of 4902 psi, 8202 feet with the magnitude of 4020 psi, and 7432 feet with the magnitude of 3776 psi, respectively. The main overpressure generating mechanism in the South Sesulu Field is non-loading mechanism, as observed from characteristics of the crossplot between sonic log and density and pore pressure profile through depth. The first encountered overpressure which is shallower to the southeast corresponds to sedimentation in the South Sesulu Field which also progrades to the southeast. The non-loading mechanism is probably caused by the clay diagenesis in forms of transformation of smectite to illite.